POTENSI PATI TEMULAWAK SEBAGAI BAHAN PANGAN PENGGANTI TEPUNG TERIGU PADA KUE BOLU - Lestari, Ema; Fatimah, Fatimah; Sandri, Dwi; Yuniarti, Retno (Jurnal Ilmu Pangan dan Hasil Pertanian, 2019)
Temulawak is one of tubers plant which grows in tropical forest areas and has good benefits for health. Temulawak also contained large enough starch, making has great potential as an additive in alternative products for processed food ingredients. Processing of temulawak starch flour is done to reduce the import of wheat flour to Indonesia. The purpose of this study are get starch of temulawak from tuber of temulawak plant, substituting wheat flour with temulawak starch flour for making sponge cake and knowing the panelist's favorite level of sponge cake made from temulawak starch flour. Sponge cake created with 3 treatments, 100% wheat flour as control, 50% temulawak starch with 50% wheat flour and 100% temulawak starch, then execute organoleptic test. Preparation of temulawak starch flour produces yellowish white flour. The organoleptic test showed that sponge cake with substitution of temulawak starch was 50% and 100% preferred over sponge cake without starch flour of temulawak. Based on this research, it was found that temulawak starch flour potency as commodity source of food substitute of wheat flour in making sponge cake because it can substitute wheat flour to 100%.